Energy and Poverty Reduction : Proceedings from a Multi-Sector and Multi-Stakeholder Workshop - How Can Modern Energy Services Contribute to Poverty Reduction? - World Bank (Washington, DC, 2014)
This report summarizes the proceedings from a workshop, the first in the region designed to foster a multi-sectoral approach to development energy services for poverty reduction, held at the Hilton Hotel in Addis Ababa, Ethiopia, October 23-25, 2002. It was co-organized by the World Bank-UNDP sponsored Energy Sector Management Assistance Program (ESMAP) and the World Bank Africa Energy Unit, and others. The report focuses on the key issues raised in the presentations and discussions which were structured around the following three themes: (a) Understanding the Energy-Poverty situation in the different countries as reflected in the Poverty Reduction Strategy Papers (PRSPs) of each country and clarified by the Ministers and country delegates; (b) Understanding the role of Energy in meeting priority objectives in the social and economic sectors of health, education, water, agriculture and development of small to medium enterprises (SMEs); and (c) Designing appropriate response initiatives in the form of draft country action plans outlining the priority energy interventions required to enhance the effectiveness of poverty reduction strategies.